Development of Encyclopedia of Sub-Materials the Role of Biodiversity in Life for Class X Based on the Results of Inventory of Medicinal Plants for Reproductive Health - Nurkholifah, Risma; Panjaitan*, Ruqiah Ganda Putri; Wahyuni, Eko Sri; Lestari, Liya Angga (Universitas Syiah Kuala, 2025)
Learning media is one component in the learning system which functions as a means of non-verbal communication. The use of learning media aims to help educators convey information so that it is easy to understand, learning becomes effective and efficient, increasing student activity and student motivation to learn. Media creation can also be developed based on the research results. The aim of this research is to determine the feasibility of a sub-material encyclopedia on the role of the biodiversity for life in class X based on the results of inventory of medicinal plants for male and female reproductive health in Balai Harapan Village, Tempunak District, Sintang Regency as a learning medium. This research uses development research methods. This development procedure consists of determining potential and problems, gathering information, designing the product, validating the design, and revising the design. The validity of the encyclopedia is obtained through content validation carried out by five validators. Encyclopedia validation is viewed from three aspects, namely presentation, content and language. Validation analysis uses Lawshe's (1975) content validity ratio (CVR) and content validity index (CVI) approaches. The research results show an average CVR of 1.00, resulting in a CVI value of 1.00 in the